Experience of young adults from divorced families - B Spalding; H G Pretorius (AOSIS, 2001)
The purpose of this study was to explore the way in which the effects of parental divorce surface during the developmental period of young adulthood. Opsomming Hierdie studie is ontwerp om die effek wat ouers se egskeiding op die ontwikkelingsfase van jong volwassenheid het, te bestudeer. *Please note: This is a reduced version of the abstract. Please refer to PDF for full text.